(untitled) (Homiletic, 2025)
The reality of trauma in the world is a call for the church, as the Christian community, to become a trauma-healing community. Therefore, this article highlights the role of the preaching ministry in the process of fulfilling this call through a trauma-aware preaching approach. This approach is grounded in an in-between theology that embraces suffering, pain, and grief as well as hope, resurrection, and redemption. Thus, the preaching approach uses eschatological hope about suffering and hope as good news. In addition, this article offers a practical application of the trauma-aware preaching approach in sermons during Lent, Triduum, and Easter.